Effects of Conditional Changes on High-Voltage Direct Current Transmission Line Characteristic - Chaichan Pothisarn; Atthapol Ngaopitakkul; Monthon Leelajindakrairerk; Natthanon Phannil; Sulee Bunjongjit; Surakit Thongsuk; Bancha Sreewirote (My University, 2022)
The high-voltage direct current (HVDC) transmission system, which links the Gurun Substation of the National Electric Authority of Malaysia (Tenaga Nasional Berhad, TNB) with the Khlong Ngae Station of the Electricity Generating Authority of Thailand (EGAT), has been extensively researched to achieve the highest quality because it is the largest of its kind in Thailand, and there is a plant to expand its transmission power. However, the impact on the whole system is under-researched. To study and develop this system, the HVDC transmission line is modelled with the MATLAB/Simulink program and a laboratory setup to investigate the effect of transmission line distance, load power, and voltage on power loss, voltage drop, and waveform. The HVDC transmission line parameters are calculated from the actual transmission line parameters and converted to the simulation model parameters using the per-unit method. The model is verified and tested by the simulation program before creating the experimental setup. The simulation and experimental results demonstrate the effects of changing system conditions via the three aspects. All the three conditions directly affect the HVDC transmission line; nevertheless, they affect each aspect differently.
Keywords: High-voltage direct current; Voltage drop; Line (geometry); Transmission system; Power transmission; High Voltage; HVDC Systems and Fault Protection